2022
DOI: 10.3390/ijms23073988
|View full text |Cite
|
Sign up to set email alerts
|

New Poly(N-isopropylacrylamide-butylacrylate) Copolymer Biointerfaces and Their Characteristic Influence on Cell Behavior In Vitro

Abstract: Designing and obtaining new synthetic smart biointerfaces with specific and controlled characteristics relevant for applications in biomedical and bioengineering domains represents one of the main challenges in these fields. In this work, Matrix-Assisted Pulsed Laser Evaporation (MAPLE) is used to obtain synthetic biointerfaces of poly(N-isopropyl acrylamide-butyl acrylate) p(NIPAM-BA) copolymer with different characteristics (i.e., roughness, porosity, wettability), and their effect on normal HEK 293 T and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Also, the surface morphology analyses revealed the presence and uniform distribution of nanopores on the material surface. 22 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, the surface morphology analyses revealed the presence and uniform distribution of nanopores on the material surface. 22 …”
Section: Resultsmentioning
confidence: 99%
“…Preliminary studies on the copolymer coating optimization showed that the surface characteristics are highly dependent on solvent, laser fluence and target concentration. 22 Therefore, in this work, in order to obtain copolymeric layers with nanoporous interfaces, fixed conditions were used: 2% pNIPAM- co -BA in DMSO (in weight concentration), laser spot measured at the target level of 1 mm 2 , fluence 350 mJ cm −2 and 72k pulses. Solutions of 2% Mel and 2% MG in distilled water were filtered through 0.22 μm Millipore membranes were placed on the samples, allowing slow evaporation under the hood at a constant temperature of 20 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports showed that, by using MAPLE for physically immobilising a wide variety of compounds, surfaces coatings could be tailored in terms of thickness, roughness, and stability in an aqueous environment [ 20 , 21 , 22 , 23 , 24 ]. Even if exposure to UV or O 2 plasma can lead to the transition toward a hydrophilic PDMS interface, the recovery of its hydrophobicity occurs within hours or days, accompanied by changes or even cracks on the surface [ 25 ].…”
Section: Introductionmentioning
confidence: 99%